Handbook of vitamin D in human health : Prevention, treatment and toxicity - Watson, Ronald Ross (Human Health Handbooks, 2013)
Research and clinical application of vitamin D has increased dramatically over the past decade stimulated by novel health promotion discoveries and documentation. This book brings together key researchers with their views focusing on the health promotion role of vitamin D. Such information is vital to clinicians, users of vitamin D supplements of all ages and those interested in public policy. The authors document and define many of the key health related roles of vitamin D. Its traditional application in bone and muscle health as well as therapy of arthritis is expanded and clarified with new research. A better understanding of the effects of vitamin D inadequacy is modelled using problems ranging from infant growth retardation to chronic kidney and periodontal disease. Uniquely the vitamin?s role in resistance and treatment of infectious diseases is shown in examples ranging from HIV/AIDS to tuberculosis. Mechanistic understanding of vitamin D's actions is enhanced by looking into its effects on immune modulation and inflammation. Expansion of the role of sunlight in stimulating vitamin D production is discussed relative to the reduction in a variety of cancers. Clearly vitamin D is like a two edged sword with great benefits but also some risks. This book provides carefully defined examples of both situations.